Do serial troponins predict the need for cardiac evaluation in trauma patients after ground-level fall? - Rachael A Callcut; Alyssa R Bellini; James T Ross; Madelyn Larson; Skyler Pearson; Anamaria J Robles (Trauma Surgery & Acute Care Open)
Purpose Troponin T levels are routinely checked in trauma patients after experiencing a ground-level fall to identify potential cardiac causes of syncope. An elevated initial troponin prompts serial testing until the level peaks. However, the high sensitivity of the test may lead to repeat testing that is of little clinical value. Here, we examine the role of serial troponins in predicting the need for further cardiac workup in trauma patients after sustaining a fall.Methods Retrospective review of all adult trauma activations for ground-level fall from January 1, 2021 to December 31, 2021 in patients who were hemodynamically and neurologically normal at presentation. Outcomes evaluated included need for cardiology consult, admission to cardiology service, outpatient cardiology follow-up, cardiology intervention and in-hospital mortality.Results There were 1555 trauma activations for ground-level fall in the study period. The cohort included 560 patients evaluated for a possible syncopal fall, hemodynamically stable, Glasgow Coma Scale score of 15, and with a troponin drawn at presentation. The initial median troponin was 20 ng/L (13–37). Second troponin values were drawn on 58% (median 33 ng/L (22–52)), with 42% of patients having an increase from first to second test. 29% of patients had a third troponin drawn (median 42 ng/L (26–67)). The initial troponin value was significantly associated with undergoing a subsequent echo (p=0.01), cardiology consult (p<0.01), admission for cardiac evaluation (p<0.01), cardiology follow-up (p<0.01), and in-hospital mortality (p=0.01); the initial troponin was not associated with cardiac intervention (p=0.91). An increase from the first to second troponin was not associated with any of outcomes of interest. Analysis was done with cut-off values of 30 ng/L, 50 ng/L, 70 ng/L, and 90 ng/L; a troponin T threshold of 19 ng/L was significant for cardiology consult (p=0.01) and cardiology follow-up (p=0.04). When the threshold was increased to 50 ng/L, it was also significant for admission for cardiac issue (p<0.01). When the threshold was increased to 90 ng/L, it was significant for the same three outcomes and in-hospital mortality (p=0.04).Conclusion The initial serum troponin has clinical value in identifying underlying cardiac disease in patients who present after ground-level fall; however, that serial testing is likely of little value. Further, using a cut-off of >50 ng/L as a threshold for further clinical evaluation would improve the utility of the test and likely reduce unnecessary hospital stays and costs for otherwise healthy patients.Level of evidence Level III.